THE IMPACT OF THE DOMESTIC AND FOREIGN MACROECONOMIC NEWS ANNOUNCEMENTS ON THE TURKISH STOCK MARKET - Ibrahim Yasar GOK; Sefa TOPUZ (Financial Studies, 2016)
This study investigates the impacts of the US and domestic macroeconomic news announcements on the Turkish stock market volatility. We analyze the GARCH volatilities behaviour of Borsa Istanbul (BIST) 100 stock index around announcement and nonannouncement days. We test 13 US and 8 Turkish macroeconomic news announcements and used daily data for the period 01.04.2010- 12.31.2015. We find that both US and Turkish GDP news announcements and also US new residential sales have significant impacts by increasing the volatility, which indicates the increasing uncertainty in these news announcements days. On the other hand, the total US and total domestic macroeconomic news effects do not have significant impacts on the BIST 100 volatility. Since the world stock markets integration can be investigated with respect to the macroeconomic news announcements of developed markets, our results indicate that Turkish stock market is less integrated and suggest portfolio diversification opportunities for international investors regarding Turkish stock market.